A Health Index for Patient Selection: A Value Function Approach with Application to Chronic Renal Failure Patients - Pliskin, Joseph S.; Beck, Clyde H. (Management Science, 1976)
Concrete criteria are needed for patient selection for scarce medical treatments and ranking of patient urgency for, or salvageability by, a given form of treatment. The mathematical theory of multi-attribute value functions is employed to rank order chronic renal failure patients with regard to therapeutic expectations. Order-2 mutual preferential independence was observed, thus an additive value function was justified. The paper demonstrates two different procedures for assessing a value function over a discrete attribute. The proposed approach yields a rank ordering (health status index) consistent with the physician's preferences and judgment. It can be employed for any medical decision process, even when only weaker preferential independence properties apply.